Let's solve each equation step by step.
First Equation:
\[ -4(2x - 11) = 12 \]
-
Distribute \(-4\): \[ -8x + 44 = 12 \]
-
Subtract \(44\) from both sides: \[ -8x = 12 - 44 \] \[ -8x = -32 \]
-
Divide by \(-8\): \[ x = \frac{-32}{-8} = 4 \]
Second Equation:
\[ -3(-4x - 3) = -27 \]
-
Distribute \(-3\): \[ 12x + 9 = -27 \]
-
Subtract \(9\) from both sides: \[ 12x = -27 - 9 \] \[ 12x = -36 \]
-
Divide by \(12\): \[ x = \frac{-36}{12} = -3 \]
Summary of Solutions:
- For the first equation, \(x = 4\).
- For the second equation, \(x = -3\).